2020
DOI: 10.1002/ange.202007804
|View full text |Cite
|
Sign up to set email alerts
|

PST‐24: A Zeolite with Varying Intracrystalline Channel Dimensionality

Abstract: Herein we report the synthesis, structure solution, and catalytic properties of PST‐24, a novel channel‐based medium‐pore zeolite. This zeolite was synthesized via the excess fluoride approach. Electron diffraction shows that its structure is built by composite cas‐zigzag (cas‐zz) building chains, which are connected by double 5‐ring (d5r) columns. While the cas‐zz building chains are ordered in the PST‐24 framework, the d5r columns adopt one of two possible arrangements; the two adjacent d5r columns are eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…9 More recently, the new zeolite PST-24, possessing randomly dispersed open and closed valves, presents local variations in channel dimensionality and high yields for the production of butadiene from 1,3-butanediol. 10 Further, interesting and improved catalytic performances have been demonstrated for several 2D zeolites possessing a faster molecular diffusion to active sites, but the high impact of the presence of these sites at the more disordered external crystal surface has also been recognized. 11 Using an assemblydisassembly-organization-reassembly (ADOR) route, it has also been shown that the internal surface area, and the related adsorptive properties, can be continuously tuned by varying the stacking of layered intermediates in a statistical, and thus non-ordered, fashion.…”
Section: Introductionmentioning
confidence: 99%
“…9 More recently, the new zeolite PST-24, possessing randomly dispersed open and closed valves, presents local variations in channel dimensionality and high yields for the production of butadiene from 1,3-butanediol. 10 Further, interesting and improved catalytic performances have been demonstrated for several 2D zeolites possessing a faster molecular diffusion to active sites, but the high impact of the presence of these sites at the more disordered external crystal surface has also been recognized. 11 Using an assemblydisassembly-organization-reassembly (ADOR) route, it has also been shown that the internal surface area, and the related adsorptive properties, can be continuously tuned by varying the stacking of layered intermediates in a statistical, and thus non-ordered, fashion.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, imidazolium cations have received much attention as nonquaternary ammonium OSDA cations in the synthesis of zeolites . Although initial studies only produced known zeolites, imidazolium OSDAs have later afforded the synthesis of silica (ITQ-12, HPM-1 , ), aluminosilicate ( RTH , PWO , PWW , , PST-24), and germanosilicate zeolites (NUD-1, NUD-2, NUD-3, CIT-13, HPM-7, HPM-8, HPM-12, HPM-14, HPM-16, and PST-35), sometimes with totally new structures. The structural richness of germanosilicate zeolites is, however, counterbalanced by the fact that four-coordinated germanium atoms in a zeolite framework are typically prone to hydrolysis and framework extraction by contact with moisture after calcination.…”
Section: Introductionmentioning
confidence: 99%
“…Imidazolium cations have allowed the synthesis of many new zeolites [3] . For instance, some small‐sized imidazolium cations are good templates for several pure‐silica zeolites, including ITW , [9] STW , [10,11] RTH , [12] or novel aluminosilicate zeolites, including PWO and PWW , [13,14] and PST‐24 [15] . Also, benzyl substituted imidazolium cations were used to discover several novel large and/or extra‐large pore germanosilicate zeolites [16–20] .…”
Section: Introductionmentioning
confidence: 99%